Why are children still being infected with HIV? Experiences in the prevention of mother-to-child transmission of HIV in south London. Issue 1 (27th September 2006) - McDonald, C; Lambert, J; Nayagam, D; Welz, T; Poulton, M; Aleksin, D; Welch, J
Abstract : Objectives: To evaluate the effectiveness of interventions to prevent mother-to-child transmission of HIV at a large teaching hospital in South East London, and to assess reasons for the small numbers of transmissions that continue to occur. Design: A database of all pregnant women diagnosed as HIV positive between 1993 and 2005 was reviewed, with detailed (retrospective) case-note review of all mother–infant pairs where HIV transmission occurred. Setting: King's College Hospital, London, UK, a teaching hospital serving an ethnically diverse and socially deprived population. Results: 296 pregnancies to 274 women were recorded. 9 of 296 (3.0%) women were lost to follow-up before the end of the pregnancy. Of 287 pregnancies followed up until after delivery, 6 (2.1%) resulted in HIV infection in the infant. More recently, between 2000 and 2004, this transmission rate was even lower, at 3 in 231 (1.3%). Each of these six women had complications, including late presentation to services and defaulting follow-up appointments, which were likely to increase the risk of HIV transmission. Four of the six transmissions occurred in utero. Conclusion: The overall transmission rate of 2% attests to the efforts of the multidisciplinary care team in managing this population which is often hard to reach. Clearly, good systems are needed to trace those women who default. Further data are needed regarding in utero transmissions.